KNEE LAXITY MEASUREMENT IN ACUTE KNEE TRAUMA AND ACL EVALUATION WITH THE ROLIMETER. Issue 22 (1st November 2016) - Ericsson, D; Östenberg, A Hafsteinsson; Alricsson, M
Abstract : The Rolimeter is an instrument that quantifies anterior knee laxity and has in previous studies showed satisfactory results regarding intra- and inter test reliability in subjects without injuries or with chronic ACL deficiency. The aim of the present study was to test reliability of the Rolimeter in the acute phase following a substantial knee trauma. The repeatability of the test procedure was also investigated. Totally 15 subjects (aged 22.7±6.9) with acute knee trauma were examined by one single observer at three different times with the Rolimeter (arthrometer model, Aircast, Europa) using maximum force. Both injured and non-injured knees were examined and anterior posterior displacement was recorded. Endpoint examination was used as "golden standard" in data analysis. The results showed strong significant correlations for the Rolimeter scores of knee laxity between baseline and endpoint for both injured and non-injured knees (r=0.928, p<0.01 and r=0.987, p<0.01 respectively). Mean differences in anterior laxity were small with no significant differences between readings. High repeatability was found in repeated measurements with no significant change over time for the non-injured knees. The study implicates that the Rolimeter produces reliable quantification of anterior knee laxity in repeated measurements even in the acute phase following knee trauma. In combination with manual tests the Rolimeter seems to be a valuable instrument in diagnosing ACL injuries.